Chiral Asymmetric Polarizations Generated by Bioinspired Helical Carbon Fibers to Induce Broadband Microwave Absorption and Multispectral Photonic Manipulation. Issue 11 (28th April 2022) - Huang, Lingxi; Duan, Yuping; Shi, Yupeng; Ma, Xinran; Pang, Huifang; Zeng, Qingwen; Che, Renchao
Abstract: Chirality, in which electromagnetic characteristic promotes asymmetric polarization, is expected to realize broadband absorption for microwave absorption materials (MAMs). Herein, inspired by the microstructure of nepenthes, a scalable approach is reported for fabricating hierarchical‐chiral helical carbon fibers with broadband microwave absorption as well as multispectral chiral manipulation. The chiral potential barriers are established by applying helically distributed stress to the fiber, which induce helical electric dipoles via positive and negative charges accumulated at the potential barriers. The states of polarization loss by Debye relaxation are 2, 3, and 4 in the samples with achirality, single‐chirality, and dual‐chirality, respectively; the polar vector of achiral electric dipoles is transformed into pseudovectors through chiral potential barriers to improve the synergistically magnetic loss, and the grade of chirality is quantified based on symmetry breaking theory. The single‐chiral fibers reach strongest absorption peak value of −30.67 dB at 2.96 GHz (carbon content is 50 wt%), and the dual‐chiral fibers achieve effective absorption bandwidth (RL ≤ −10 dB) of 8.8–18 GHz. In addition to microwaves, the chiral photonic manipulation plays a role in near‐ultraviolet and visible spectra. The present discovery points to a pathway for using chiral model to open up new microwave absorption mechanism and integrated application. Abstract : In order to take advantage of the chiral asymmetric polarization to realize broadband microwave absorption, the present work proposes a novel chiral carbon fiber with hierarchical helices, in which helical electric dipoles induce a new mechanism of electromagnetic synergistic attenuation. The fibers also generate multispectral chiral photonic manipulation to point to a pathway to new integrated application of chiral materials.